The effect of advanced footwear technology on elite male marathon race speed - Langley, J. O.; Langley, B. (European Journal of Applied Physiology, 2023)
Purpose The aim of this study was to explore the ergogenic effect of advanced footwear technology (AFT) upon world-class male marathon running speed.